Does Institutional Ownership Moderate the Effects of CAR, Tax Avoidance, and CSR on Firm Value? Evidence from the Indonesian Banking Industry - Muhammad Aimar Gimnastyar; Mochammad Ridwan Ristyawan; Anggraini Syahputri; Wendy; Uray Ndaru Mustika (Politeknik Ganesha Medan, 2026)
This study aims to examine the effects of Capital Adequacy Ratio (CAR), Tax Avoidance, and Corporate Social Responsibility Disclosure (CSRD) on firm value in banks listed on the Indonesia Stock Exchange that meet the eligibility criteria from 2020 to 2024, as well as to evaluate the role of Institutional Ownership (IO) as a moderating variable. The sample was selected using purposive sampling, resulting in 27 banks with a total of 125 observations. Data were analyzed using panel data regression with moderated regression analysis (MRA), employing both Random Effects Model (REM) and Fixed Effects Model (FEM) to investigate the direct and moderating effects among the variables. The results indicate that CAR has a positive and significant effect on firm value, confirming its role as a key indicator of financial stability and market confidence in the banking sector. In contrast, Tax Avoidance does not significantly affect firm value, while CSRD also shows no direct significant impact. Moderation analysis reveals that IO strengthens the positive effect of CAR on firm value, does not significantly moderate the relationship between Tax Avoidance and firm value, and negatively moderates the effect of CSRD on firm value. These findings highlight the importance of capital adequacy as a primary financial signal and suggest that institutional investors are selective in responding to CSR practices. The study provides practical implications for investors, banking management, and regulators in enhancing corporate governance and improving the interpretation of financial signals in the Indonesian banking sector